2018
DOI: 10.3847/1538-4357/aac6e9
|View full text |Cite
|
Sign up to set email alerts
|

Glycinamide, a Glycine Precursor, Caught in the Gas Phase: A Laser-ablation Jet-cooled Rotational Study

Abstract: Glycinamide, a glycine precursor, has been successfully generated in the gas phase by laser ablation of its hydrochloride salt, and its microwave spectrum, recorded from 6 to 16 GHz using a Chirped Pulse Fourier Transform Microwave (LA-CP-FTMW) spectrometer, is reported for the first time. The existence of a single structure stabilized by a Na–H ⋯ NtH2 hydrogen bond has been revealed in the supersonic expansion. The complex nuclear quadrupole coupling hyperfine structure due to the two 14N nuclei has been comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…This fact is also supported by the low interconversion barrier from syn-anti to syn-syn SA (9.3 kJ mol À1 ). However,o nt he low-frequency side of each m b -type R-branch transition of the anti-anti conformer,v ery weaks ets of the same R-branch progressions could be identified and were indeed ascribed to the 13 Ci sotopologs in their natural abundance (1.109 %) with doubled intensity owing to the existence of two equivalent carbons [see Figure 4(a)].T he sensitivity attained with our laser ablationb roadband chirped pulse Fourier transformm icrowave spectroscopy (LA-CP-FTMW)t echnique was not sufficient to observe the 18 Om onosubstituted speciesd espite its enhanceda bundance (0.410 %d ue to the C 2v symmetry). We took advantage of the high sensitivity of our narrowbandL A-MB (molecular beam)-FTMW spectrometer [23,24] for the observation of 18 Oi sotopologs [see Figure4(b)].…”
Section: Rotational Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…This fact is also supported by the low interconversion barrier from syn-anti to syn-syn SA (9.3 kJ mol À1 ). However,o nt he low-frequency side of each m b -type R-branch transition of the anti-anti conformer,v ery weaks ets of the same R-branch progressions could be identified and were indeed ascribed to the 13 Ci sotopologs in their natural abundance (1.109 %) with doubled intensity owing to the existence of two equivalent carbons [see Figure 4(a)].T he sensitivity attained with our laser ablationb roadband chirped pulse Fourier transformm icrowave spectroscopy (LA-CP-FTMW)t echnique was not sufficient to observe the 18 Om onosubstituted speciesd espite its enhanceda bundance (0.410 %d ue to the C 2v symmetry). We took advantage of the high sensitivity of our narrowbandL A-MB (molecular beam)-FTMW spectrometer [23,24] for the observation of 18 Oi sotopologs [see Figure4(b)].…”
Section: Rotational Spectrummentioning
confidence: 99%
“…Coupled with laser ablation techniques, it enables the transfer of organic and biological molecules from the solid state to the gas phase and allows them to be probed in the isolated environment of a supersonic expansion . By using this powerful strategy, most of the amino acids and several relevant biological molecules, as well as species of astrophysical interest, such as glycinamide, have been recently revealed. Also, new gas‐phase experiments exploring not only the conformational landscape of squaric acid but its microsolvated complexes should represent an essential source of reference data to understand its inherent inter‐ and intramolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hypothesis that this compound could be a precursor of glycine by hydrolysis, the addition of one molecule of water would give the glycinamide intermediate. The microwave spectrum of this compound was recently published (Alonso et al 2018), but the millimeter wave spectrum is still missing. On the other hand, this is not the case of glycolamide, a glycine isomer, whose millimeter wave spectrum was recorded very recently (Sanz-Novo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with laser-ablation techniques, it enables an ultra-fast vaporization of organic and biological molecules and allows them to be probed in the isolated environment of a supersonic expansion (Alonso et al 2014). With this outstanding strategy, several relevant biomolecules and most of the amino acids (Alonso et al 2015), as well as species of astrophysical interest, such as hydantoin (Alonso et al 2017) and glycinamide (Alonso et al 2018), have recently been revealed.…”
Section: Introductionmentioning
confidence: 99%